Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/soc4.12544
|View full text |Cite
|
Sign up to set email alerts
|

The sociology of grit: Exploring grit as a sociological variable and its potential role in social stratification

Abstract: This paper proposes the currently fashionable psychological notion of "grit" as a potentially useful variable in sociological analysis and explores its potential for contributing to addressing sociological concerns. Grit, comprising perseverance and passion toward longterm goals, has received growing attention within academia and from the general public as a strong predictor of achievement. Grit captures an important, noncognitive, underdeveloped aspect of agency not included in life course or stratification s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 61 publications
(97 reference statements)
0
10
0
Order By: Relevance
“…Grit and the sense of control are closely related but distinct concepts. While the sense of control captures subjective beliefs about one's agency, grit taps into more behavioral inclinations that potentially transfer one's beliefs to actual behaviors that lead to certain outcomes (Kwon 2017). These two crucial psychological resources, however, have not been empirically examined together.…”
Section: Correlates Of Grit: Sense Of Control and Conscientiousnessmentioning
confidence: 99%
“…Grit and the sense of control are closely related but distinct concepts. While the sense of control captures subjective beliefs about one's agency, grit taps into more behavioral inclinations that potentially transfer one's beliefs to actual behaviors that lead to certain outcomes (Kwon 2017). These two crucial psychological resources, however, have not been empirically examined together.…”
Section: Correlates Of Grit: Sense Of Control and Conscientiousnessmentioning
confidence: 99%
“…Furthermore it was shown that grit highly correlates with other traits such as perseverance, consistency, and the big five personality traits of conscientiousness [3,4]. It has been suggested that grit is similar to conscientiousness or that grit is or mimics conscientiousness [5], however, it is further argued that grit, although within the "conscientiousness family", is theoretically different in that it is the passion or tenacity to achieve long-term goals, rather than simply a personality trait [6][7][8]. In addition to this, grit has been argued to be more likely to determine success beyond conscientiousness, intelligence, and physical abilities [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, lower socioeconomic status children spend less time in extracurricular activities that are related to the development of grit and academic achievement (Park, 2010). In this sense, recent studies have emphasized the need for research on grit to account for the role that structural factors such as socioeconomic origins, status (i.e., the material, social, and cultural resources available to the individual) play in creating the context for grit to support behaviors that help with achievement of challenging long-term goals (Kundu, 2017; Kwon, 2017). Specifically, we propose that people who can count on higher levels of personal income will have more resources for supporting themselves in the entrepreneurial process, and this will allow them to concentrate their effort on the challenges intrinsically associated with the entrepreneurial process, thereby enhancing the relationship between grit and the probability of creating a business/becoming self-employed.…”
Section: Hypothesesmentioning
confidence: 99%
“…For example, lower socioeconomic status children spend less time in extracurricular activities that are related to the development of grit and academic achievement (Park, 2010). In this sense, recent studies have emphasized the need for research on grit to account for the role that structural factors such as socioeconomic origins and status (i.e., the material, social, and cultural resources available to the individual) play in creating the context for grit to support behaviors that help with achievement of challenging long-term goals (Kundu, 2017; Kwon, 2017).…”
Section: Introductionmentioning
confidence: 99%